A model for empowering web-based communities through the digital educational repository paradigm. (21st December 2006) - Maher, Elaine; Pathak, Pramod
In this paper, we study web-based communities and the role that they play. We also explore the role these communities can play in the development and well-being of the society in future. In reference to this, we survey Digital Educational Repositories (DER) and analyse their importance in supporting web-based communities in achieving their aims. We look at some of the more popular DERs in use today and examine how they are being used. We ask the question, is it possible to pull out a course/information on the fly from available web-based digital repositories for the benefit of web-based communities? We also propose the development of a software engine that would be able to develop appropriate content/information for web-based communities using the DER mechanism.